2017
DOI: 10.1515/jomb-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Early Substitution of Subclinical Hypothyroidism on Biochemical Blood Parameters and the Quality of Life

Abstract: SummaryBackgroundSubclinical hypothyroidism (SCH) is defined as high TSH and normal thyroxine. Data on the effects of early substitution by levothyroxine on psychophysical health in SCH are still not consistent enough to support its introduction.MethodsClinical parameters, biochemical data and quality of life (Short Form 36 questionnaire) were measured before the intervention and 3 months after the euthyroid state had been achieved in SCH patients.ResultsSignificant reduction in body weight (p=0.030), systolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 47 publications
5
30
0
1
Order By: Relevance
“…While increased nitro‐oxidative stress appears to exert its negative effects from normal to moderately low HRQoL values, CMPAase activity and TSH levels may further decrease HRQoL to the very low HRQoL range. Previously, it was observed that thyroid disorders may negatively impact QoL and that treatment with thyroid hormones may improve QoL . One explanation is that thyroid hormones mediate symptoms that play a role in HRQoL, including fatigue, feeling cold, and weight gain .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While increased nitro‐oxidative stress appears to exert its negative effects from normal to moderately low HRQoL values, CMPAase activity and TSH levels may further decrease HRQoL to the very low HRQoL range. Previously, it was observed that thyroid disorders may negatively impact QoL and that treatment with thyroid hormones may improve QoL . One explanation is that thyroid hormones mediate symptoms that play a role in HRQoL, including fatigue, feeling cold, and weight gain .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hypothalamic‐pituitary‐thyroid activity shows modest changes in MDD (lowered serum basal thyroid‐stimulating hormone [TSH] levels) and BD (increase in basal TSH), while subclinical hyperthyroidism and hypothyroidism may impact HRQoL . Treatments for subclinical hypothyroidism with thyroxine may improve HRQoL . Nevertheless, there are no data as to whether increased nitro‐oxidative stress, increased MDA and AOPP levels, and alterations in basal TSH levels could impact HRQoL among patients with mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Also, controversial statements from some studies that “subclinical hypothyroidism is a mild thyroid failure and should be treated”, 65 and from other that “the treatment of subclinical hypothyroidism is seldom necessary”, 66 make the decision to treat or not to treat these patients difficult. At present, because of the lack of long‐term outcomes studies regarding the beneficial or not effects of treatment of patients with SCH we should err on the beneficial aspect of treatment, since treatment of SCH with levothyroxine is simple, cheap and easy to administer, and is also, associated with improvement in BP, lipid changes and decreased incidence of CHD and HF 33,48‐49,51‐53,65‐72 . Overall, treatment of SCH is more beneficial in younger patients, but les beneficial in older patients (≥75 years of age).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previous studies, there are several other studies that demonstrate a beneficial effect of treatment in patients with SCH 47‐53 . The data from these studies are summarised in Table 3 and they will be, briefly, discussed here.…”
Section: Treatment Of Subclinical Hypothyroidismmentioning
confidence: 99%
See 1 more Smart Citation